2012
DOI: 10.1590/s0044-59672012000300007
|View full text |Cite
|
Sign up to set email alerts
|

Biomass production and essential oil yield from leaves, fine stems and resprouts using pruning the crown of Aniba canelilla (H.B.K.) (Lauraceae) in the Central Amazon

Abstract: Aniba canelilla (H.B.K.) Mez. is a tree species from Amazon that produces essential oil. The oil extraction from its leaves and stems can be an alternative way to avoid the tree cutting for production of essential oil. The aim of this study was to analyse factors that may influence the essential oil production and the biomass of resprouts after pruning the leaves and stems of A. canelilla trees. The tree crowns were pruned in the wet season and after nine months the leaves and stems of the remaining crown and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Sangwan et al (2001) rightly emphasized that essential oil helps plants to adapt to environmental stresses (drought, intense radiation, and high temperature) and is also involved in defense mechanisms against pests. This hypothesis was corroborated by Manhaes et al (2012), in Aniba canelilla (Lauraceae) a tree growing in the Amazon rainforest. These authors showed that essential oil yield of resprouts was inversely correlated with canopy openness, i.e., light increased the yield of essential oil.…”
Section: Trees Situatedmentioning
confidence: 61%
“…Sangwan et al (2001) rightly emphasized that essential oil helps plants to adapt to environmental stresses (drought, intense radiation, and high temperature) and is also involved in defense mechanisms against pests. This hypothesis was corroborated by Manhaes et al (2012), in Aniba canelilla (Lauraceae) a tree growing in the Amazon rainforest. These authors showed that essential oil yield of resprouts was inversely correlated with canopy openness, i.e., light increased the yield of essential oil.…”
Section: Trees Situatedmentioning
confidence: 61%
“…Regarding the parts of the plant, its yield of the stem is higher in the dry seasons. Leaf yield, however, does not appear to be influenced by such factors (Taveira et al, 2003;Manhães et al, 2012).…”
Section: Essential Oilmentioning
confidence: 88%
“…Its chemical composition has two main constituents, 1-nitro-2-phenylethane (1N2PE), the first known natural nitro derivative which is generally pointed as the major component and is responsible for the cinnamon-like odor characteristic of the species, and methyleneugenol (Gottlieb and Magalhães, 1959;Gottlieb and Magalhães, 1960a;Oger et al, 1994;Maia et al, 2001;Taveira et al, 2003;Lima et al, 2004;Da Silva et al, 2007;Maia and Andrade, 2009;Silva et al, 2009;Sousa, 2011;Manhães et al, 2012;Vale et al, 2013;Almeida et al, 2017;Farias et al, 2017;Giongo et al, 2017). These substances were identified both in the stem wood, bark, and leaves.…”
Section: Essential Oilmentioning
confidence: 99%
See 2 more Smart Citations